Pengaruh Kualitas Produk, Keragaman Produk, Dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Di Kulo Coffe - Syahwa Renada Amelia Santoso; Meylani Tuti (Human Capital Development, 2023)
This study aims to determine the effect of product quality, product variety, and electronic word of mouth on purchasing decisions at Kopi Kulo. The population in this study are Kulo coffee buyers. This sampling technique uses accidental sampling and a total sample of 154 people is obtained. This study uses data analysis techniques with SEM with the help of SmartPLS. The results show that product quality has a positive and significant effect on purchasing decisions, product variety has no effect on purchasing decisions, and e-WOM has a positive and significant effect on purchasing decisions.